86. Antibiotic-resistant gram-negative bacterial infections among persons with or without a prior positive test for SARS-CoV-2 in 10 U.S. sites, 2020. (15th December 2022) - Bulens, Sandra N; Grass, Julian E; Duffy, Nadezhda; Tola, Jigsa; Jacob, Jesse T; Smith, Gillian; Vaeth, Elisabeth; Dumyati, Ghinwa; Looi, Hsioa Che; Phipps, Erin C; Flores, Kristina; Wilson, Christopher; et al.
Abstract: Background: The Centers for Disease Control and Prevention's Emerging Infections Program (EIP) conducts active laboratory- and population-based surveillance for carbapenem-resistant Enterobacterales (CRE), extended spectrum beta-lactamase-producing Enterobacterales (ESBL-E), and carbapenem-resistant Acinetobacter baumannii (CRAB) in 10 U.S. sites. To describe the impact of the COVID-19 pandemic on the epidemiology of these antibiotic-resistant gram-negative bacteria (AR-GNB), we assessed characteristics of AR-GNB patients with and without a prior SARS-CoV-2 positive (SC2+) viral test. Methods: In 2020 among EIP catchment-area residents, an incident CRAB or CRE case was defined as the first isolation of A. baumannii complex, Escherichia coli, Enterobacter cloacae complex, Klebsiella aerogenes, K. oxytoca, K. pneumonia, or K. variicola in a 30-day period resistant to ≥1 carbapenem (excluding ertapenem for CRAB) from a normally sterile site or urine. An incident ESBL-E case was defined as the first isolation of E. coli, K. pneumonia, or K. oxytoca in a 30-day period resistant to any third-generation cephalosporin and non-resistant to all carbapenems from a normally sterile site or urine. Patient charts were reviewed. Results: Of 3904 AR-GNB cases with data available, 163 (4%) had a prior SC2+ test (85 ESBL-E, 70 CRE, and 8 CRAB). Median time from the most recent SC2+ test to AR-GNB culture date was 20 days (IQR 1–48 days). AR-GNB cases with a SC2+ test versus those without were more likely to be Black, non-Hispanic than another race/ethnicity (31% vs 15%; P< 0.0001), aged ≥65 years (62% vs 52%; P=0.0139), and to have prior healthcare exposures (63% vs 49%; P=0.0003) and indwelling devices (51% vs 28%; P< 0.0001). They were also more likely to have bacteremia (24% vs 11%; P< 0.0001), pneumonia (6% vs 1%; P< 0.0001) and be hospitalized around the time of their AR-GNB culture (67% vs 36%; P< 0.0001); median time from SC2+ test to hospital admission was 0.5 day (IQR 0–29.5 days). Conclusion: AR-GNB infections preceded by a SC2+ test were rare but more severe and associated with more healthcare risk factors. This underscores the need for continued infection prevention and control practices and monitoring of these infections during the COVID-19 pandemic. Disclosures: Ghinwa Dumyati, MD, Pfizer: Grant/Research Support.